The importance of pedagogical technologies in teaching chemistry - Ismatova Nozima Rakhmatilloevna (Zien Journals, 2023)
Since the independence of the Republic of Uzbekistan, we have witnessed a sharp increase in the need for qualified and mature specialists. Educating independent thinking boys and girls starting from school is one of the urgent tasks of this day. The young generation should not only learn a certain amount of knowledge, but also possess the spirituality and enlightenment characteristic of the builder of an independent state, and its attitude to work and behavior should be envied by everyone
Keywords: Chemistry; teaching methodology; chemical reaction